Annotated record of the detailed examination of Mn deposits from the ARIES-5 cruise among the West Pacific Guyots - Bruce C Heezen; J L Matthews; Giulio Catalano; James H Natland; Laurence A Coogan; Mary Tharp; M Rawson (PANGAEA, 1973)
The sea floor of the western Pacific is covered by five stratigraphic units: (l) an eastward thinning wedge of late Tertiary silty clay, primarily of volcanic origin, (2) a Cretaceous to Tertiary zeolitic red clay, (3) a Late Cretaceous to Tertiary chalk/chert sequence, (4) a Cretaceous clay, and (5) a basal chalk/chert sequence. The basal chalk was deposited on the young crust at the crest of the mid-oceanic ridge, while the upper chalk was deposited beneath the equator, and the abyssal clays were deposited in abyssal depths in mid latitudes. A kinematic model has been constructed that outlines the deposition of these units on growing crust, which not only was displaced westward away from the accretion center of the mid-oceanic ridge, but northward under the equator. The average northward component of motion for the Pacific plate has been 2 cm per year from 0 to 30 m.y. and 4.4 cm per year from 30 to 100 m.y. The deep-sea deposits of the Pacific are basically and systematically time transgressive. Claims of general synchroneity for either lithostratigraphy or acoustostratigraphy are rejected as inconsistent with both the drilling data and the kinematic model of Pacific pelagic stratigraphy. A few more well sampled holes in the ancient Pacific plate combined with an appropriately refined kinematic model should yield a extquotesinglerather detailed history of the Pacific plate since the Jurassic.
Supplement to: Heezen, BC et al. (1973): Western Pacific Guyots. In: Heezen, B.C.; MacGregor, I.D., Initial Reports of the Deep Sea Drilling Project, Initial Reports of the Deep Sea Drilling Project, U.S. Government Printing Office, XX, 653-723, https://doi.org/10.2973/dsdp.proc.20.132.1973